CULTURE SHOCK EXPERIENCES OF INDONESIAN UNIVERSITY STUDENTS IN TEACHING PRACTICE AND COMMUNITY SERVICE IN THAILAND - Dian Sri Wahyuni (Abjadia, 2019)
This study was designed to explore culture shock experiences faced by Indonesian university students in doing teaching practice and community service in southern border province Thailand, and to describe the strategies used to deal with cultural differences and problems. There were thirty eight students of university from twelve universities in Indonesia who responded to the open-ended questionnaires sent by the writer through google docs link. The data were analysed using grounded theory code as basis for the thematic analysis. The findings revealed that there were six culture shock experienced by Indonesian university students, namely: language and communication problems, life style and cultural differences, social support and making friends, positive experiences, academic problems, and psychological problems. The most dominant shock experience faced by Indonesian university students was positive experiences. As for the strategies to deal with cultural differences and problems, there were found four strategies used by Indonesian university students, namely: self-confidence and optimism, accepting new culture, seeking social support, and language training. The most strategy mentioned by Indonesian university students was accepting new culture.